A New Approach to Detect and Prevent Wormhole in Wireless Sensor Network Using AD-AODV - Tamilarasi, N; Santhi, S.G (International Journal of Computer Sciences and Engineering, 2018)
Now-a-days wireless networks are needed for mobile communication that makes wired communication impossible. The characteristics of WSN are small battery, restricted bandwidth and dynamic topology that expose Wireless Sensor Networks (WSN) to various kinds of attacks such as Black hole, Wormhole, Selective forwarding, Sink hole etc., . Therefore proper security measures will be taken while implementing WSN. Among all those attacks, wormhole attack is the most powerful attack in sensor networks. In this paper, a novelty routing protocol called attack detection ad hoc on demand distance vector (AD-AODV) is proposed to detect and prevent wormhole attack in wireless sensor network. This protocol needs no special hardware and software for the implementation. Moreover it is based on round trip time (RT), threshold round trip time (TRT) and the hop count for detecting the wormhole node. Network simulator2 (NS2) is used for implementing the proposed work.